2012
DOI: 10.1093/heapol/czs077
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and inequity in access to health care and treatment for chronic conditions in China: the Guangzhou Biobank Cohort Study

Abstract: Non-communicable diseases (NCDs) are a large and rapidly-growing problem in China and other middle-income countries. Clinical treatment of NCDs is long-term and expensive, so it may present particular problems for equality and horizontal equity (equal treatment for equal need) in access to health care, although little is known about this at present in low- and middle-income countries. To address this gap, and inform policy for a substantial proportion of the global population, we examined inequality and inequi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
45
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 41 publications
12
45
1
1
Order By: Relevance
“…Over the same period of time, study participants’ hypertension awareness significantly increased from 22.9% in 1997 to 33.7% in 2000, 34.9% in 2004, and 42.7% in 2006. These findings suggest that higher income levels may enable older adults to have better access to health care services and routine check-ups, which is consistent with previous studies (33). Nevertheless, further study is required to examine how income is associated with hypertension awareness among older Chinese adults.…”
Section: Discussionsupporting
confidence: 92%
“…Over the same period of time, study participants’ hypertension awareness significantly increased from 22.9% in 1997 to 33.7% in 2000, 34.9% in 2004, and 42.7% in 2006. These findings suggest that higher income levels may enable older adults to have better access to health care services and routine check-ups, which is consistent with previous studies (33). Nevertheless, further study is required to examine how income is associated with hypertension awareness among older Chinese adults.…”
Section: Discussionsupporting
confidence: 92%
“…It also emerged that AYUSH use is relatively low among patients in the middle MPCE quintiles. To some extent, this is similar to the Chinese and Nepalese experience where traditional medicine use is more among higher income households [38,39]. In fact, after adjusting for socioeconomic and demographic variables, we did not observe any significant rural-urban differentials in use of AYUSH services for outpatient care though urban households were more likely to seek medical advice for such care.…”
Section: Discussionsupporting
confidence: 81%
“…Another study in China reported pro‐rich inequality and inequity in the treatment among people with chronic diseases . In addition, health insurance, education and occupation also contributed to inequality in accessing care . Our findings did not show any significant factors relating to outpatient and inpatient care, suggesting better awareness of control of blood sugar given diabetes.…”
Section: Discussioncontrasting
confidence: 64%